2012
DOI: 10.1152/jn.00107.2012
|View full text |Cite
|
Sign up to set email alerts
|

The brain matters: effects of descending signals on motor control

Abstract: The ability of nerve cords and spinal cords to exhibit fictive rhythmic locomotion in the absence of the brain is well-documented in numerous species. Although the brain is important for modulating the fictive motor output, it is broadly assumed that the functional properties of neuronal circuits identified in simplified preparations are conserved with the brain attached. We tested this assumption by examining the properties of a novel interneuron recently identified in the leech (Hirudo verbana) nerve cord. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…The slow oscillatory bursting behavior observed here when ATP was applied to the isolated ganglion might arise from the passive inputs of a central pacemaker cell. For example, an oscillatory bursting pattern of similar period and duration, has been attributed to the central pattern generator for crawling in the leech (Mullins & Friesen, ; Puhl & Mesce, ). This phasic activity is characterized by alternating activation of ventral and dorsal motoneurons with a 5–25 s period, which underlies the two‐step elongation—contraction cycle responsible for crawling behavior (Puhl & Mesce, ).…”
Section: Discussionmentioning
confidence: 99%
“…The slow oscillatory bursting behavior observed here when ATP was applied to the isolated ganglion might arise from the passive inputs of a central pacemaker cell. For example, an oscillatory bursting pattern of similar period and duration, has been attributed to the central pattern generator for crawling in the leech (Mullins & Friesen, ; Puhl & Mesce, ). This phasic activity is characterized by alternating activation of ventral and dorsal motoneurons with a 5–25 s period, which underlies the two‐step elongation—contraction cycle responsible for crawling behavior (Puhl & Mesce, ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the significant correlation between DA-DN spike rates and leg movement speed, we found that bidirectional manipulations of DA-DN activity had no effect on ongoing leg movements. Given the abundant evidence that the brain provides brakes on the output of body motor circuits that are absent in reduced preparations (M'Cracken 1907;McDaniel and Horsfall 1957;Brodfuehrer and Friesen 1986;Thompson 1986;Mullins and Friesen 2012), one interpretation of these data is that with all descending pathways intact, activation of DA-DNs is not sufficient to alter ongoing leg movements in the behavioral contexts we examined. A related possibility is that the effects of DA-DN inputs to downstream motor circuits must combine with changes in other neuromodula- tory inputs to generate a detectable effect on leg movements, although it remains unknown whether and how other neuromodulatory neurons are recruited during leg movements in flies.…”
Section: Effects Of Acute Manipulations Of Da-dn Spike Rate On Ongoinmentioning
confidence: 97%
“…Molecular sequence information for the Northwestern European medicinal leech Hirudo medicinalis has more recently been accumulating through studies targeting specific candidate gene sequences [ 9 14 ], tissue types [ 15 , 16 ], or life stages [ 17 ]. The Southeastern European medicinal leech Hirudo verbana has not received the same attention in the surge to bring transcriptomic approaches to traditionally “non-genetic” systems, even though it remains the most commonly used species in neurophysiological and behavioral studies [ 18 21 ]. While H .…”
Section: Introductionmentioning
confidence: 99%